Evidence for two spin-glass transitions with magnetoelastic and magnetoelectric couplings in the multiferroic (B i1-x B ax)(F e1-x T IX) O3 system - Kumar A.; Kaushik S.D.; Siruguri V.; Pandey D. (My University, 2025)
For disordered Heisenberg systems with small single ion anisotropy (D), two spin-glass (SG) transitions below the long-range ordered (LRO) phase transition temperature (Tc) have been predicted theoretically for compositions close to the percolation threshold. Experimental verification of these predictions is still controversial for conventional spin glasses. We show that multiferroic spin-glass systems can provide a unique platform for verifying these theoretical predictions via a study of change in magnetoelastic and magnetoelectric couplings, obtained from an analysis of diffraction data, at the spin-glass transition temperatures (TSG). Results of macroscopic (dc M(H, T), M(t), ac susceptibility [χ (ω, T)], and specific heat (Cp)) and microscopic (x-ray and neutron scattering) measurements are presented on disordered BiFeO3, a canonical Heisenberg system with small single ion anisotropy, which reveal appearance of two spin-glass phases, SG1 and SG2, in coexistence with the LRO phase below the Almeida-Thouless (A-T) and Gabey-Toulouse (G-T) lines. It is shown that the temperature dependence of the integrated intensity of the antiferromagnetic (AFM) peak shows dips with respect to the Brillouin function behavior around the SG1 and SG2 transition temperatures. The temperature dependence of the unit cell volume departs from the Debye-Grüneisen behavior below the SG1 transition and the magnitude of departure increases significantly with decreasing temperature up to the electromagnon driven transition temperature below which a small change of slope occurs followed by another similar change of slope at the SG2 transition temperature. The ferroelectric polarization also changes significantly at the two spin-glass transition temperatures. These results, obtained using microscopic techniques, clearly demonstrate that the SG1 and SG2 transitions occur on the same magnetic sublattice and are intrinsic to the system. We also construct a phase diagram showing all the magnetic phases in the BF-xBT system. While our results on the two spin-glass transitions support the theoretical predictions, they also raise several open questions, which need to be addressed by revisiting the existing theories of spin-glass transitions after taking into account the effect of magnetoelastic and magnetoelectric couplings as well as electromagnons. © 2018 American Physical Society.